The Anthropological and Social Consequences of the Triadic Logic: A Proposal for Adapting the Logic Model to Life Thinking - Teresa Aizpun (Religions)
Modernity is characterised by a specific scientific paradigm based on binary logic. Neither freedom nor creativity have a place in this logical model. On the contrary, triadic logic enables rational consideration of an anthropological and social model compatible with both things: freedom and creativity, and therefore with Christianity. Furthermore, triadic logic provides us with a model of thought compatible with the current physical explanation of reality.